2012
DOI: 10.1016/j.ijscr.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Tunneled modified lotus petal flap for surgical reconstruction of severe introital stenosis after radical vulvectomy

Abstract: Tunneled lotus petal flaps represents a feasible, attractive and versatile surgical reconstructive technique that can be easily performed after surgical treatment of vulvoperineal neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Although various locoregional flaps are described in the literature for post-oncological vulvoperineal reconstruction [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], their use in managing vulvar stenosis is less documented. One case report by Buda et al [ 12 ] reported the use of a tunneled modified lotus petal flap for vulvar reconstruction in a severe case of introital stenosis following radical vulvectomy. Other authors have employed rhomboid transposition flaps [ 8 ], pudendal–thigh flaps [ 13 ], and V-Y fascio-cutaneous advancement flaps [ 28 ] to address small vulvovaginal defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various locoregional flaps are described in the literature for post-oncological vulvoperineal reconstruction [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], their use in managing vulvar stenosis is less documented. One case report by Buda et al [ 12 ] reported the use of a tunneled modified lotus petal flap for vulvar reconstruction in a severe case of introital stenosis following radical vulvectomy. Other authors have employed rhomboid transposition flaps [ 8 ], pudendal–thigh flaps [ 13 ], and V-Y fascio-cutaneous advancement flaps [ 28 ] to address small vulvovaginal defects.…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical treatments, such as topical creams and vaginal dilators, are largely ineffective in treating scar tissue constriction and the narrowing of the vaginal introitus, often necessitating a surgical approach. To our knowledge, there have been few reports describing the surgical repair of introital stenosis, with most using principles of plastic surgery involving techniques such as Z-plasty [ 6 ], vertical or horizontal tissue excision [ 7 , 8 ], split-thickness or full-thickness skin grafts [ 9 ], and local and regional flaps [ 10 , 11 , 12 , 13 ]. This study aims to describe the outcomes in a series of patients who underwent surgery for the correction of vulvar stenosis involving the vaginal introitus or the urethral meatus, and who were reconstructed using capillary perforator flaps harvested from the perineum, describing the surgical technique used.…”
Section: Introductionmentioning
confidence: 99%